PSIKOEDUKASI PENTINGNYA KESEHATAN MENTAL PADA TUNA SUSILA DI MATTIRO DECENG - Tri Sulastri; Rieska Cendra Ayu Wardhani; Nurul Yuanuary Amir; Bunga Shabrina Aprilianti; Dian Tiovany Nainggolan; Muh Fadhil Marwan (Universitas Negeri Makassar, 2023)
A woman chooses to sell her body to make ends meet, due to several factors. Not only is the economy the main reason for working as a sex worker, but also family and social environment factors. From these factors a person easily experiences psychological instability, especially when undergoing a rehabilitation period with a feeling that they have not accepted the new status condition of being a beneficiary. Therefore, community service is carried out by psychoeducation using non-training methods to find out whether there is an effect of psychoeducation on the importance of mental health for the Prosecutors in Mattiro Deceng. Psychoeducation is based on the One-Group Pretest-Postest Design method. Participants who participated were 32 people, from the age range of 16 years to 47 years and were female. Based on the results of data processing from a comparison of pre-test and post-test scores for each participant, it shows that 20 respondents experienced an increase in understanding of mental health, as many as 10 participants did not experience an increase in point 1, and as many as 2 participants did not experience an increase in point 2. Thus, there is an increase in understanding between the pre-test and post-test of providing psychoeducation to beneficiaries (PSK) at UPT PPSKW Mattiro Deceng. It is hoped that further community service can develop and reach a wider audience.